How do the component skills affect Chinese FL reading comprehension? A study based on ridge regression analysis - Zhong, Kai; Wong, Ling Yann; Yong, Mei Fung; Ng, Boon Sim (De Gruyter Mouton, 2023)
This study aimed to investigate the effect of reading components (including Chinese character knowledge, morphological knowledge, vocabulary knowledge, grammar knowledge, and lexical inference) on the reading comprehension of 44 Malaysian child learners of Chinese as a foreign language (CFL). Measures of Chinese character knowledge, morphological knowledge, receptive vocabulary, vocabulary synonym, lexical inference, word order, grammatical judgment, and reading comprehension were used. Drawing upon ridge regression, the study found that grammar knowledge (measured by word order and grammatical judgment) had the largest effect on reading comprehension, followed by morphological knowledge and vocabulary knowledge (measured by receptive vocabulary and vocabulary synonym). Lexical inference and Chinese character knowledge had the least effects on reading comprehension. The findings of the study are discussed with pedagogical implications and future research suggestions.